2022
DOI: 10.3390/dj10070138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries in Children in Mymensingh and Its Associated Risk Factors: A Cross-Sectional Study

Abstract: Background: Children suffer from various oral and periodontal diseases. Dental caries is one of the most prevalent oral diseases among children in the world. This study was conducted to identify the prevalence and risk factors of dental caries in children in Mymensingh, Bangladesh. Methods: A cross-sectional study was conducted on 362 pediatric patients who attended the Dental Unit of Mymensingh Medical College from March to September 2019. The sample size was calculated using a statistical formula and the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
8
1
1
Order By: Relevance
“…They appear in large quantities in saliva, on the dorsum of the tongue, mucous membranes, the hard palate, dental plaque and, in smaller numbers, on tooth surfaces throughout a child's earliest years of life [15]. Aside from microflora, other risk factors, particularly obesity and tooth caring, are linked to microbially associated inflammatory disease affecting tooth-supporting structures [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They appear in large quantities in saliva, on the dorsum of the tongue, mucous membranes, the hard palate, dental plaque and, in smaller numbers, on tooth surfaces throughout a child's earliest years of life [15]. Aside from microflora, other risk factors, particularly obesity and tooth caring, are linked to microbially associated inflammatory disease affecting tooth-supporting structures [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has consistently shown that children with low socio-economic status face a heightened susceptibility to ECC. A myriad of factors contributes to this increased risk, including financial constraints ( 3 ), restricted access to dental services ( 21 ), limited knowledge of effective oral hygiene practices ( 9 ), and insufficient resources for proper dental care ( 22 ). Furthermore, unhealthy dietary habits, such as the consumption of sugary snacks and beverages ( 23 ), exacerbate the prevalence of dental caries within low-income communities.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent poverty and income inequality contribute to a higher incidence of ECC among children from lower socioeconomic backgrounds in Bangladesh. Multiple risk factors, such as low maternal education, inadequate nutrition, poor oral hygiene practices, limited access to dental care, and environmental factors, contribute to this problem ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most multifactor prediction models for caries risk have been designed with a cross-sectional approach, which limits the ability to establish causality between variables. [ 5 6 7 ] Abdel Fattah et al . [ 8 ] studied dental caries in Egypt's population-based survey, analyzing data from 9457 participants.…”
Section: Introductionmentioning
confidence: 99%